The question of access and spatial justice in universities in sub-Saharan Africa: A capabilities approach - Nomanesi Madikizela-Madiya (Transformation in Higher Education, 2021)
Background: The discussions related to access in higher education collate enrolment with the provision of education. Yet, when considering what the university education should provide, some enrolments still restrict capabilities, freedom and rights to quality education. The article argues that the debates regarding access to higher education are incomplete without addressing this divide.